2020
DOI: 10.1186/s40249-020-00644-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking patterns after HIV diagnosis or antiretroviral treatment initiation: a global systematic review and meta-analysis

Abstract: Background: Tobacco consumption is more life-threatening in people living with human immunodeficiency virus (HIV) than within the general population; therefore, people living with HIV (PLWH) should be highly motivated to take action towards quitting smoking at or after HIV diagnosis. The aim of this systematic review with meta-analysis was to investigate changes in smoking habits among PLWH over time. Main text: We considered prospective and retrospective cohort studies including PLWH aged 15 years and above, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…It is beyond the scope of this review to determine the reasons for increased smoking prevalence among PLH, but some hypotheses are useful to consider. A review by Nansseu et al found that trends in tobacco smoking among PLH changed little over time, indicating a low quit rate [89] . An analysis of 184 PLH who smoked in San Francisco found high rates of psychological co-morbidity, unemployment and illicit drug use [90] , all of which are positively associated with tobacco consumption [91,92] .…”
Section: Discussionmentioning
confidence: 99%
“…It is beyond the scope of this review to determine the reasons for increased smoking prevalence among PLH, but some hypotheses are useful to consider. A review by Nansseu et al found that trends in tobacco smoking among PLH changed little over time, indicating a low quit rate [89] . An analysis of 184 PLH who smoked in San Francisco found high rates of psychological co-morbidity, unemployment and illicit drug use [90] , all of which are positively associated with tobacco consumption [91,92] .…”
Section: Discussionmentioning
confidence: 99%
“…Both HIV-itself and tobacco smoking are associated with numerous health concerns including but not limited to cancer, cardiovascular diseases, hypertension, lung diseases, diabetes, tuberculosis, immune system diseases, and chronic obstructive pulmonary disease [7,[28][29][30][31]. Therefore, curbing the burden of tobacco smoking in PLHIV on ART is paramount and requires efficient interventions against this modifiable behavior and risk factor since ART initiation do not favor quitting smoking [32]. The high active smoking prevalence found in this study calls all HIV healthcare providers to pay more attention to this dreadful public health concern and to integrate quitting tobacco interventions in already built The findings of this review should be interpreted considering some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of 17,995 PLHIV in Europe and North America estimated that PLHIV lose more years of life from tobacco smoking than from HIV itself [6]. Reasons for the high rates of tobacco use among PLHIV are complex and overlapping [9], and include socioeconomic determinants such as unemployment, lower education or income levels [10][11][12], experiences of mental illness and/or substance use disorders [13][14][15], and/or using tobacco to manage stress associated with living with HIV [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the negative health impacts of tobacco smoking for PLHIV [4,[6][7][8], a recent systematic review and meta-analysis found that HIV diagnosis or treatment initiation did not typically result in quitting smoking [9]. Evidence suggests that many PLHIV have attempted to quit tobacco smoking; however, most attempts are unsuccessful [18][19][20].…”
Section: Introductionmentioning
confidence: 99%